Routine insulin sliding scale protocol versus software driven algorithm (star protocol) for blood glucose management of critically ill patients in the ICU: A prospective observational study / Tan Ru Yi - Tan, Ru Yi (2018)
The objective of the study was to evaluate a specifically designed software driven algorithm for the establishment of tight glycaemic control with lesser risks of potentially harmful hypoglycaemia in critically ill patients in the ICU and to compare the results with the routine glucose management protocol i.e. insulin sliding scale, used by the ICU in UMMC. A total of 82 patientï¿½s that were admitted to the ICU requiring glucose management protocols were recruited for this study. This was a prospective observational study conducted over a duration of 1 year. Biometric data, feeding and fluid regimens, vital signs and laboratory parameters (haematological, metabolic and biochemical results) were extracted and collected from the patientï¿½s hospital ICU records. The data collected was subsequently simulated with the software driven algorithm (STAR protocol) and results were analysed to determine if it was better at maintaining blood glucose levels within set targets of 6-10 mmol/L. Analysis of the entire cohort showed that statistically there was no significant difference between the ISS protocol with the STAR protocol in maintaining glucose control within the set targets of 6-10 mmol/L with a p-value of 0.1556, z-value of -1.42404 and U value of 2928.5. However, the incidence of severe hypoglycaemic events (BG < 2.2 mmol/L) was 0.05% using the ISS arm whereas there was no incidence of hypoglycaemia in the STAR protocol arm. Despite both arms showing similar performance in terms of BG therapy, there is still much room for improvement with the STAR protocol as simulations were made based on Caucasian population pharmacokinetic and pharmacodynamics models. Hence, further work and research in the area of software development and customisation to local epidemiology is required to validate it for use in our clinical practice.